The Role of Peer Counselors in the Promotion of Student Discipline in Ugunja Sub-County, Kenya - Osodo, John Mark; Osodo, Joseph; Mito, Jane Wagumba; Raburu, Pamela; Aloka, Peter (Asian Journal of Education and Training, 2016)
In spite of the existence of guidance and counseling services in schools in Siaya County for the management of discipline, in 2012, 32 schools went on the rampage. This scenario was suspected to be occasioned by lack of an effective alternative strategy to contain student indiscipline. The purpose of this study was to determine the role of peer counseling in promoting discipline among students in public secondary schools in Ugunja Sub-County, Kenya. The study adopted descriptive survey design. The population of the study comprised of 3500 students from public secondary schools. The researchers used the Table of Krejcie and Morgan to determine the sample size of 246. Instruments for data collection were questionnaires and interview schedules. Piloting was done in 4 institutions to obtain the instruments reliability. Face validity of the instruments was ascertained by the experts from the Department of Psychology and Educational Foundations. Quantitative data was analyzed using descriptive statistics such as frequency counts, and percentages. Qualitative data was analyzed using thematic analysis. The study findings indicated that peer counseling has a significant role in promoting discipline among students in public secondary schools. The study recommends that peer counselors should be motivated in order for them to perform optimally.